2009
DOI: 10.4028/www.scientific.net/kem.419-420.381
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Force and Acoustic Emission Sensors for Detecting Tool Damage in Turning Processes

Abstract: Condition monitoring systems of manufacturing processes have been recognised in recent years as one of the key technologies that provide the competitive advantage in many manufacturing environments. It is capable of providing an essential means to reduce cost, increase productivity, improve quality and prevent damage to the machine or work-piece. Turning operations are considered one of the most common manufacturing processes in industry. Despite recent development and intensive engineering research, the deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The sensitivity of condition monitoring system. This research builds on the Automated Sensor and Signal Processing Selection (ASPS) approach [5] to investigate further combination of techniques and parameters using a wide range of signal analysis and simplification techniques. The proposed monitoring system consists simplification the collected signals and measuring the sensitivity of the sensors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensitivity of condition monitoring system. This research builds on the Automated Sensor and Signal Processing Selection (ASPS) approach [5] to investigate further combination of techniques and parameters using a wide range of signal analysis and simplification techniques. The proposed monitoring system consists simplification the collected signals and measuring the sensitivity of the sensors.…”
Section: Resultsmentioning
confidence: 99%
“…Automated Sensor and Signal Processing Selection (ASPS) approach [5] has been implemented to define the most sensitive features (SCF) which are constructed from the sensor and the signal processing method. Linear regression slop method used to measure the sensitivity of the signal, then these values combined with the real roughness measurements using surface tester.…”
Section: Resultsmentioning
confidence: 99%
“…Many researchers have used AE for monitoring the turning process while Teti et al [8] investigated additional milling and drilling processes. Bhuiyan et al [26] used AE for monitoring turning and evaluating tool condition, while Al-Habaibeh et al [27] applied additionally force measurement for that purpose. Because the tool condition has a great impact on treatment conditions and the same on quality of the product, that aspect was considered [28].…”
Section: Introductionmentioning
confidence: 99%
“…However, it was observed that such models had difficulty estimating approximation errors and therefore required development to capture uncertainties during the turning process. Al-Habaibeh et al 11 and Fang et al 12 used multiscale methods, both of which were based on a milling force signal. Their research demonstrated the usefulness of the milling force, and the designed systems were able to predict tool wear successfully.…”
Section: Introductionmentioning
confidence: 99%